Class Counts: Education, Inequality, and the Shrinking Middle Class - Ornstein, Allan (Rowman & Littlefield Publishers, 2007)
Class counts. Class differences and class warfare have existed since the beginning of western civilization, but the gap in income and wealth between the rich (top 10 percent) and the rest has increased steadily in the last twenty-five years. The U.S. is heading for a financial oligarchy much worse than the aristocratic old world that our Founding Fathers feared and tried to avoid. The middle class is struggling and shrinking, the Medicare and Social Security trusts are drying up, and education is no longer the great equalizer. A moral society, one that is fair and just, sets limits on the accumulation of wealth and inherited privilege and also guarantees a safety net for the less fortunate. This book describes the need for a redistribution of wealth in order to make U.S. society more democratic, fair and just, and outlines the ways in which we can begin to make these very necessary changes. This is a timely and powerful book, one that should be read by anyone interested in preserving the social fabric of American life.